Understanding the states and dynamics of mangrove forests in land cover transitions of The Gambia using a Fourier transformation of Landsat and MODIS time series in Google Earth Engine - Liman Harou, Issoufou; Inyele, Julliet; Minang, Peter; Duguma, Lalisa (Frontiers in Forests and Global Change, 2023)
Mangroves are resilient forests of transitional zones between land, ocean and freshwater for they are tolerant to salinity. In The Gambia, mangrove forests are found along the coast of Atlantic Ocean and River Gambia where they support the livelihoods of millions through multiple ecosystems services. Despite their importance in The Gambia, consistent country-wide information on their coverage, dynamics and change hotspots are lacking. Thus far, it remains unclear whether the coverage of mangroves has decreased or increased over the last few decades. The existing estimates vary strongly across sources and the methodologies in the available literature are not always reproducible. This study attempts to fill these gaps by providing up-to-date spatial information on mangrove forests in The Gambia. To provide a reproducible workflow and a comprehensive assessment, we used continuous time series of freely available data to study the extent and dynamics of mangrove forests in The Gambia. To construct gap-free image time series, we used statistical models to describe land surface phenology based on monthly composites derived from Landsat and MODIS land surface reflectance acquired between 2000 and 2020. We used 1212 Landsat and 407 MODIS tiles spread across multiple spectral indices along with a calibrated set of training and validation data to train and validate a random forest classifier for accurate land cover classifications. The overall accuracy and Kappa statistics of the classifications range between 0.96 and 0.98. Our findings suggest a net increase of 4,000 ha in mangrove forests over the last 2 decades, corresponding to an annual rate of 200 ha. The net increase is largely due to strong policy making which results in participative forest resource management through the national forest action plan. The net increase in mangrove forests should not mask the substantial degradation in some places across the country. We estimated a total loss of nearly 5,670 ha, most of which appears to have taken place during the last decade in favor of wetlands. The Gambian mangroves are amongst the most promising green business in Gulf of Guinea, deserving an integrated governance - policy framework that address the key requirements for ecological sustainability.